Immunity to Neisseria meningitidis Group B in Adults despite Lack of Serum Bactericidal Antibody - Welsch, Jo Anne (American Society for Microbiology (ASM), 2007)
Serum-complement-mediated bactericidal antibody (SBA) remains the serologic hallmark of protection against meningococcal disease, despite experimental and epidemiologic data that SBA may underestimate immunity. We measured bactericidal activity against three strains of Neisseria meningitidis group B in sera from 48 healthy adults and in whole blood from 15 subjects. Blood was anticoagulated with lepirudin, a specific thrombin inhibitor not known to activate complement. Depending on the test strain, protective SBA titers of ≥1:4 were present in only 8 to 15% of the subjects, whereas bactericidal activity was present in 40 to 87% of subjects according to the blood assay. Among SBA-negative subjects, blood from 23 to 42% gave a decrease of ≥2 log(10) CFU/ml after 1 h of incubation, and blood from 36 to 83% gave a decrease of ≥1 log(10) after 2 h. For most blood samples, bactericidal antibodies primarily were directed against noncapsular antigens, since activity was not inhibited by group B polysaccharide. For some SBA-negative subjects, white cells were not needed, since similar respective bactericidal activities were observed in blood and plasma. Bactericidal activity by whole blood of SBA-negative subjects can be rapid (<1 h) and effective (≥2 log(10)) and, among all subjects, was four- to sixfold more prevalent than a positive SBA. Thus, while an SBA titer of ≥1:4 predicts protection against meningococcal disease, a titer of <1:4 is poorly predictive of susceptibility. More sensitive assays than SBA are needed to assess protective meningococcal immunity, or we risk underestimating the extent of immunity in the population and the effectiveness of new meningococcal vaccines.